2011
DOI: 10.1115/1.4004641
|View full text |Cite
|
Sign up to set email alerts
|

Technical and Economic Evaluation of a Formic Acid/Hydrogen Peroxide Fuel Cell System With Pt-M/C as Anode Catalyst

Abstract: Cell performance of formic acid/hydrogen peroxide (HCOOH/H2O2) fuel cell, using commercial Pt-Ru/C, and prepared Pt-M/C (M = Ir, Mo, Co, Ag, W, Ni, Sn) bimetallic catalysts as anode catalysts are experimentally investigated and reported in this paper. Corresponding to cell performance, electrocatalytic activity of the system using commercially available and prepared catalysts is evaluated by linear sweep voltammetry technique (LSV). The result shows that the system using 20%Pt-10%Sn/C yields better formic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…[ 115 ] Further, research on a formic acid/hydrogen peroxide (HCOOH/H 2 O 2 ) fuel cell emphasized the superior formic acid oxidation reaction of the 20% Pt‐10%Sn/C system. [ 116 ] Lastly, a study on an alkaline aluminium hydrogen peroxide semi‐fuel cell demonstrated its capability to power the autonomous underwater vehicle for extended underwater surveys. [ 117 ] Briefly touching upon other notable studies, research on Pt‐Cu bimetallic nanoparticles showcased the Pt50Cu50/C catalyst's superior catalytic activity in direct borohydride‐H 2 O 2 FCs (DBHFCs).…”
Section: Materials Requirements For H2o2 Fcmentioning
confidence: 99%
“…[ 115 ] Further, research on a formic acid/hydrogen peroxide (HCOOH/H 2 O 2 ) fuel cell emphasized the superior formic acid oxidation reaction of the 20% Pt‐10%Sn/C system. [ 116 ] Lastly, a study on an alkaline aluminium hydrogen peroxide semi‐fuel cell demonstrated its capability to power the autonomous underwater vehicle for extended underwater surveys. [ 117 ] Briefly touching upon other notable studies, research on Pt‐Cu bimetallic nanoparticles showcased the Pt50Cu50/C catalyst's superior catalytic activity in direct borohydride‐H 2 O 2 FCs (DBHFCs).…”
Section: Materials Requirements For H2o2 Fcmentioning
confidence: 99%
“…3 Additionally, the use of hydrogen peroxide as the oxidant can substantially increase the theoretical voltage of fuel cells and thus improve cell performance. [5][6][7][8][9][10][11][12][13] However, there are three issues associated with the direct reduction of hydrogen peroxide in fuel cells. [5][6][7][8][9][10][11][12][13] However, there are three issues associated with the direct reduction of hydrogen peroxide in fuel cells.…”
mentioning
confidence: 99%
“…4 For these reasons, much effort has been devoted to the development of hydrogen peroxide-based fuel cells. [5][6][7][8][9][10][11][12][13] However, there are three issues associated with the direct reduction of hydrogen peroxide in fuel cells. First, the actual cathode potential (0.8 V to 0.9 V vs. SHE) is much lower than the theoretical one (1.78 V vs. SHE), which is mainly attributed to the mixed potential resulting from the simultaneous hydrogen peroxide oxidation reaction (HPOR) on the cathode.…”
mentioning
confidence: 99%